AB0100 Monocytes Differentiated from IPS Cells Derived from Rheumatoid Arthritis Patients Express More M-Scf-Receptor Together with Rank Than Those from Healthy Donors Resulting in the Accelerated Osteoclastgenesis. (9th June 2015) - Ito, M.N.; Murakami, M.; Saito, M.; Niwa, A.; Osawa, M.; Nakahata, T.; Nishimoto, N.
Abstract : Background: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic proliferation of synovial cells and destructive polyarthritis. Bone destruction in RA is mediated by increased numbers of osteoclasts, and the enhanced osteoclastgenesis has been reported in RA. However, it remains unclear whether or not the genetic factors influence the increased osteoclastgenesis in RA. To answer this question, we induced osteoclasts in vitro using induced pluripotent stem cells (iPSC) derived from RA-patients and non-onset family members of the patients (NOR). Objectives: The aim of this study is to clarify if the osteoclastgenesis in RA is enhanced genetically compare to NOR. Methods: iPSCs have been established from skin fibroblasts from RA patients and NORs. Under monocytes-induced conditions in vitro, floating cells were sequentially collected and subsequently inoculated onto glass chamber slides with M-CSF and RANKL. An osteoclast was defined as a TRAP-positive cell containing at least three nuclei. To analyze the bone resorption activity, the fluorescent-intensity of FITC-labeled chondroitin sulfate (CS), which is released from the calcium phosphate layer resolved by osteoclasts, was measured in the culture supernatant by a fluorimeter. The expressions of osteoclast markers (cathepsin K and MMP-9) in osteoclasts induced from monocytes collected on day 24 and day 32, and osteoclast-precursor markers (CD115: MCSF-receptor, and RANK) in the monocytes collected on days 24, 28 and 32 after induction from iPSCs were analyzed by either RT-PCR or fluorescence-activated cell sorting using the corresponding antibodies. Results: Osteoclastgenesis of monocytes derived from RA-iPSCs increased as compared to that of NOR-iPSCs. The TRAP positive cell numbers per well of RA patients were higher than those of NOR in the presence of RANKL (25 ng/mL and 100 ng/mL) at all 6 time points as shown in the figure below. The fluorescent-intensity of FITC-labeled CS in the culture supernatant of osteoclasts differentiated from RA-iPSCs was also higher than that of NOR-iPSCs (fluorescent intensity/well; 4869±838 and 954±252, respectively on day24). The expression of cathepsin K and MMP9 on day24 were also increased in osteoclasts from RA-iPSCs by 20 and 12 times higher than osteoclasts from NOR-iPSCs, respectively. The proportion of CD115-positive cells in CD14-positive cells was increased in monocytes induced from RA-iPSCs. Furthermore, monocytes induced from RA-iPSCs highly expressed RANK mRNA as compared with those of NOR-iPSCs at all day points of harvesting monocytes. Conclusions: The genetically up-regulated M-CSF receptor and RANK in the osteoclast precursors in RA-iPSC may lead to the enhanced osteoclastgenesis. Disclosure of Interest: None declared